The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/929750
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Structural Stability and Electronic and Elastic Properties of Helium inα-Zirconium

Abstract: First-principles calculations within density functional theory have been performed to investigate the behaviors of helium inα-zirconium. The most favorable interstitial site for He inα-Zr is not an ordinary tetrahedral or octahedral site, but a basal octahedral site with a formation energy as low as 2.40 eV. The formation energy reduces to 1.25 eV in the presence of preexisting vacancies. The analysis on the density of states and the charge density has been carried out. In addition, the influences of He and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The most significant modifications were observed at around −1.05 eV and −6.70 eV, whereas a new peak has appeared at around −5.93 eV, which is mainly due to the admixture of He s and Pd d orbitals with a small contribution from tritium s orbitals and Pd s and p orbitals. A DFT study by Zheng et al also found a peak at −1.00 eV for He-s orbitals [31], and the repulsive interaction between Pd d and He s states might be the reason for the modification of the DOS at this energy level [29].…”
Section: Electronic Structuresmentioning
confidence: 94%
“…The most significant modifications were observed at around −1.05 eV and −6.70 eV, whereas a new peak has appeared at around −5.93 eV, which is mainly due to the admixture of He s and Pd d orbitals with a small contribution from tritium s orbitals and Pd s and p orbitals. A DFT study by Zheng et al also found a peak at −1.00 eV for He-s orbitals [31], and the repulsive interaction between Pd d and He s states might be the reason for the modification of the DOS at this energy level [29].…”
Section: Electronic Structuresmentioning
confidence: 94%
“…Recently, several density functional theory (DFT) calculations have been conducted to investigate the effects of vacancy on the mechanical properties of Zr. Zheng et al [15] calculated the elastic constants of Zr with a single vacancy. They found an increase in C11, C33, C44 and a decrease in C12 and C13.…”
Section: Introductionmentioning
confidence: 99%
“…α-Zr crystallizes in a close-packed hexagonal structure with a space group of P 63/ mmc . We optimized the unit cell structure using experimental geometry from ref (see Table ). Our calculated values of the lattice parameters were a = 3.249 Å and c = 5.136 Å, and they are in good agreement with the experimentally measured values: a = 3.221 Å and c = 5.141 Å and the previously calculated values by Domain and Jomard .…”
Section: Resultsmentioning
confidence: 99%
“…Unit cell structure of α-Zr with two Zr atoms (Zr1 and Zr2, in green) (a); tetragonal and octagonal sites in a unit cell (b). Octahedral and tetrahedral sites as represented, respectively, by O1, O2 and T1, T2, T3, T4 are shown explicitly (c) in which the data were obtained from ref .…”
Section: Resultsmentioning
confidence: 99%